The critical temperature of the two-dimensional ± J Ising spin glass - R. Sungthong (2018)
We have studied the two-dimensional ± J Ising model on the square lattice with a view to determine whether a spin glass can exist at small finite temperatures. By mapping the Ising model onto an ensemble of non-interacting lattice fermions, we have shown that the critical temperature for the spin glass phase transition appears to vanish. This result applies for all concentrations of negative bonds where the ground state is a spin glass.